Research in personnel and human resources management, vol. 31. - Martocchio, Joseph J.; Joshi, Aparna; Liao, Hui (Bingley : Emerald Group Publishing Limited, 2012)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 31 of Research in Personnel and Human Resources Management (RPHRM) contains six papers on important issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field. This collection of papers represents excellent scholarship and illustrates the truly interdisciplinary character of the field.
Includes bibliographical references.
oif 18/06/14
Loan
Keywords: Personnel management; Personnel management -- Research